Dampak Pertumbuhan Ekonomi, Pengangguran, dan Tingkat Pendidikan Terhadap Kemiskinan di Provinsi Nusa Tenggara Timur, Indonesia - Sarlianus Poma (AKSIOMA : Jurnal Manajemen, 2024)
This study sought to ascertain how poverty in East Nusa Tenggara, Indonesia, was impacted concurrently and in part by economic growth, unemployment, and educational attainment. Non-participant observation was used for data gathering. Panel data analysis utilizing the Fixed Effect Model (FEM) was data analysis technique employed. The results which were based on the Eviews 9 test showed F statistic was greater than the F table (105.1927 > 2.46) or the F probability was smaller than the probability value (0.000000 < 0.05), it means poverty in East Nusa Tenggara, Indonesia, was positively and significantly impacted by economic growth, unemployment, and education levels simultaneously between 2015 and 2019. Meanwhile, partially 2015 to 2019, economic growth (T value 0.344914 < Ttable 1.65936 and probability value 0.7310 > ? = 0.05), unemployment (T value 1.194274 < Ttable of 1.65936 and probability value 0.2357 > ? = 0.05) and educational attainment (T value -0.546285 < Ttable 1.65936 and probability value 0.5863 > ? = 0.05) had a negative and negligible impact on poverty in the province of East Nusa Tenggara, Indonesia.